Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! Let's go through the step-by-step solution to graph the quadratic equation [tex]\( y = x^2 + 6x + 8 \)[/tex]. We will identify the [tex]$y$[/tex]-intercept, the [tex]$x$[/tex]-intercepts, and the vertex of the parabola.
### Step 1: Identify the [tex]$y$[/tex]-intercept
The [tex]$y$[/tex]-intercept of a quadratic equation [tex]\( y = ax^2 + bx + c \)[/tex] is found by setting [tex]\( x = 0 \)[/tex] and solving for [tex]\( y \)[/tex].
[tex]\[ y = (0)^2 + 6(0) + 8 = 8 \][/tex]
So, the [tex]$y$[/tex]-intercept is at [tex]\( (0, 8) \)[/tex].
### Step 2: Identify the [tex]$x$[/tex]-intercepts
The [tex]$x$[/tex]-intercepts of a quadratic equation are the points where [tex]\( y = 0 \)[/tex]. To find these, we solve the equation:
[tex]\[ x^2 + 6x + 8 = 0 \][/tex]
Using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1, b = 6, \)[/tex] and [tex]\( c = 8 \)[/tex]:
[tex]\[ x = \frac{-6 \pm \sqrt{6^2 - 4 \cdot 1 \cdot 8}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{36 - 32}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{4}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm 2}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{-6 + 2}{2} = \frac{-4}{2} = -2 \][/tex]
[tex]\[ x = \frac{-6 - 2}{2} = \frac{-8}{2} = -4 \][/tex]
So, the [tex]$x$[/tex]-intercepts are at [tex]\( (-2, 0) \)[/tex] and [tex]\( (-4, 0) \)[/tex].
### Step 3: Identify the vertex
The vertex of a quadratic equation [tex]\( y = ax^2 + bx + c \)[/tex] occurs at:
[tex]\[ x = -\frac{b}{2a} \][/tex]
Substituting [tex]\( a = 1 \)[/tex] and [tex]\( b = 6 \)[/tex]:
[tex]\[ x = -\frac{6}{2 \cdot 1} = -3 \][/tex]
Now, calculate the [tex]$y$[/tex]-coordinate by substituting [tex]\( x = -3 \)[/tex] back into the quadratic equation:
[tex]\[ y = (-3)^2 + 6(-3) + 8 \][/tex]
[tex]\[ y = 9 - 18 + 8 \][/tex]
[tex]\[ y = -1 \][/tex]
So, the vertex is at [tex]\( (-3, -1) \)[/tex].
### Step 4: Graphing the equation
1. Plot the [tex]$y$[/tex]-intercept at [tex]\( (0, 8) \)[/tex].
2. Plot the [tex]$x$[/tex]-intercepts at [tex]\( (-2, 0) \)[/tex] and [tex]\( (-4, 0) \)[/tex].
3. Plot the vertex at [tex]\( (-3, -1) \)[/tex].
4. Draw a parabolic curve passing through these points, opening upwards, as the coefficient of [tex]\( x^2 \)[/tex] is positive.
This creates the graph of the quadratic equation [tex]\( y = x^2 + 6x + 8 \)[/tex], showing all the key features:
- [tex]$y$[/tex]-intercept at [tex]\( (0, 8) \)[/tex]
- [tex]$x$[/tex]-intercepts at [tex]\( (-2, 0) \)[/tex] and [tex]\( (-4, 0) \)[/tex]
- Vertex at [tex]\( (-3, -1) \)[/tex]
The graph would look like a parabola opening upwards, with the mentioned points highlighted.
### Step 1: Identify the [tex]$y$[/tex]-intercept
The [tex]$y$[/tex]-intercept of a quadratic equation [tex]\( y = ax^2 + bx + c \)[/tex] is found by setting [tex]\( x = 0 \)[/tex] and solving for [tex]\( y \)[/tex].
[tex]\[ y = (0)^2 + 6(0) + 8 = 8 \][/tex]
So, the [tex]$y$[/tex]-intercept is at [tex]\( (0, 8) \)[/tex].
### Step 2: Identify the [tex]$x$[/tex]-intercepts
The [tex]$x$[/tex]-intercepts of a quadratic equation are the points where [tex]\( y = 0 \)[/tex]. To find these, we solve the equation:
[tex]\[ x^2 + 6x + 8 = 0 \][/tex]
Using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1, b = 6, \)[/tex] and [tex]\( c = 8 \)[/tex]:
[tex]\[ x = \frac{-6 \pm \sqrt{6^2 - 4 \cdot 1 \cdot 8}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{36 - 32}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{4}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm 2}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{-6 + 2}{2} = \frac{-4}{2} = -2 \][/tex]
[tex]\[ x = \frac{-6 - 2}{2} = \frac{-8}{2} = -4 \][/tex]
So, the [tex]$x$[/tex]-intercepts are at [tex]\( (-2, 0) \)[/tex] and [tex]\( (-4, 0) \)[/tex].
### Step 3: Identify the vertex
The vertex of a quadratic equation [tex]\( y = ax^2 + bx + c \)[/tex] occurs at:
[tex]\[ x = -\frac{b}{2a} \][/tex]
Substituting [tex]\( a = 1 \)[/tex] and [tex]\( b = 6 \)[/tex]:
[tex]\[ x = -\frac{6}{2 \cdot 1} = -3 \][/tex]
Now, calculate the [tex]$y$[/tex]-coordinate by substituting [tex]\( x = -3 \)[/tex] back into the quadratic equation:
[tex]\[ y = (-3)^2 + 6(-3) + 8 \][/tex]
[tex]\[ y = 9 - 18 + 8 \][/tex]
[tex]\[ y = -1 \][/tex]
So, the vertex is at [tex]\( (-3, -1) \)[/tex].
### Step 4: Graphing the equation
1. Plot the [tex]$y$[/tex]-intercept at [tex]\( (0, 8) \)[/tex].
2. Plot the [tex]$x$[/tex]-intercepts at [tex]\( (-2, 0) \)[/tex] and [tex]\( (-4, 0) \)[/tex].
3. Plot the vertex at [tex]\( (-3, -1) \)[/tex].
4. Draw a parabolic curve passing through these points, opening upwards, as the coefficient of [tex]\( x^2 \)[/tex] is positive.
This creates the graph of the quadratic equation [tex]\( y = x^2 + 6x + 8 \)[/tex], showing all the key features:
- [tex]$y$[/tex]-intercept at [tex]\( (0, 8) \)[/tex]
- [tex]$x$[/tex]-intercepts at [tex]\( (-2, 0) \)[/tex] and [tex]\( (-4, 0) \)[/tex]
- Vertex at [tex]\( (-3, -1) \)[/tex]
The graph would look like a parabola opening upwards, with the mentioned points highlighted.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.